Treatment Outcomes for Adolescents With Multidrug-Resistant Tuberculosis in Lima, Peru - Dylan B. Tierney MD MPH; Meredith B. Milstein MPH; Justin Manjourides PhD; Jennifer J. Furin MD PhD; Carole D. Mitnick ScD (SAGE Publishing, 2016)
Treatment outcomes for adolescents with multidrug-resistant tuberculosis are rarely reported and, to date, have been poor. Among 90 adolescents from Lima, Peru, 68 (75.6%) achieved cure or completion of treatment. Unsuccessful treatment was less common in the Peru cohort than previously described in the literature.